Analisis Faktor Penyebab Variasi Jumlah Cat Pada Aktifitas Painting Di PT Caterpillar Indonesia Batam - Abdul Azis Sunandar; Ganda Sirait (LPPM Universitas Putera Batam, 2019)
PT Caterpillar Indonesia Batam is a limited liability company in heavy equipment industry, in making its products Caterpillar has 4 sub production process should be carried Fabrication, Machinning, Painting and Assembly in this study aimed to analyze problems that occur in the process of painting. In the production period from February 2015 through October 2016 variation amount of paint used and therefore this study will discuss and analyze the factors that cause variations in the amount of paint used in painting Truck Body 777 using Cuase And Effect analys (fishbone diagram) then proceed to determine the dominant factor with Analytical Hierarchy Process (AHP) the results obtained total weight of each factor of production, namely: human (65%), the method (62%), machinery (48%), materials (75% ), environment(50%), then gained the most dominant factors that cause variations in the amount of paint used in painting process 777 Truck Body is a material factor weighing highest score is 75%